MEMBEDAH MAKNA GREEN ACCOUNTING DI MATA PELAKU UMKM: STUDI FENOMENOLOGI PADA SENTRA INDUSTRI KERIPIK TEMPE SANAN DI KOTA MALANG - Robiatus Salamah (Universitas Muhammadiyah Gorontalo, 2025)
This study aims to explore and deeply understand the meaning of green accounting (environmental accounting) from the perspective of Micro, Small, and Medium Enterprises (MSMEs) in the Sanan Tempe Chips Industrial Center, Malang City. The research focuses on how craftsmen interpret financial sacrifices and waste management practices in maintaining business sustainability. Although green accounting is theoretically often perceived as difficult to implement by small business actors, this study seeks to capture the essence of the phenomenon through the lived experiences of MSME actors. A qualitative method with a phenomenological approach was employed. Data were collected through in-depth interviews, participatory observation, and documentation involving four key informants who are tempe chip business owners in the Sanan area. The findings reveal three main dimensions in the interpretation of green accounting: (1) accounting as social harmony (tepo seliro), where environmental costs are perceived as social investments to maintain comfort and harmony among community members; (2) collective accounting through community associations (paguyuban), reflecting shared environmental responsibility based on mutual cooperation; and (3) the spiritual dimension (barokah), in which waste utilization and adherence to customary values are understood as expressions of gratitude and efforts to attain economic blessing with spiritual value. These findings indicate that for MSMEs in Sanan, green accounting is not merely understood as a financial recording process, but as a business practice that integrates economic, social, cultural, and spiritual values. Therefore, this study recommends the development of green accounting standards that are more humanistic, contextual, and adaptive to the cultural characteristics of Indonesian MSMEs to support holistic business sustainability.